BRAF Alteration in Central and Peripheral Nervous System Tumors - Srinivasa, Komal; Cross, Kevin A.; Dahiya, Sonika (Frontiers in Oncology, 2020)
BRAF (alternately referred to as v-raf murine sarcoma viral oncogene homolog B1) is a proto-oncogene involved in the mitogen-activated protein kinase (MAPK) pathway. BRAF alterations are most commonly missense mutations or aberrant fusions. These mutations are observed in numerous primary central nervous system tumors as well as metastases. This review discusses the prevalence of BRAF alteration within select notable CNS tumors, and their prognostic associations. Included are some novel entities such as diffuse leptomeningeal glioneuronal tumor (DLGNT), polymorphous low grade neuroepithelial tumor of the young (PLNTY) and multinodular and vacuolating neuronal tumor (MVNT). Knowledge of this gene’s integrity in CNS and PNS tumors can have profound diagnostic and therapeutic implications. Also reviewed are the current state of targeted therapy against aberrant BRAF as it pertains mostly to the CNS and to a lesser extent in PNS, and certain diagnostic aspects.